Heavy-load exposed gear graphene lubricating grease and preparation method thereof
By modifying graphene oxide and combining nano-tungsten disulfide and chemical bonded anionic salt technology, a combined grease of modified graphene and base oil was prepared, which solved the friction and wear problems of heavy load open gears, and achieved multi-faceted performance improvement and service life extension of grease.
Patent Information
- Application Number
- CN202411668232.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
During the operation of heavy-load open gears, friction and wear problems are serious, resulting in decline in mechanical properties and economic losses. The existing graphene grease has poor aggregation and dispersion during the preparation process, resulting in insufficient lubrication and wear resistance.
By modifying graphene oxide, combining the synergistic effect of nanotungsten disulfide, chemical bonds are used to connect anionic salt and modified jeprosy oil, and a combined lubricating grease of modified graphene, base oil and additives are prepared through the thickening of vapor phase silica.
The lubricating wear resistance, extreme pressure, drip point, cone inlet, oil separation, evaporation loss and oxidation stability of heavy-load open gear graphene grease has been achieved, extending the service life of the grease.
Smart Images

Figure CN119529920A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubrication, and in particular to a heavy-load open gear graphene grease and a preparation method thereof. Background Art
[0002] In the process of industrial processing and production, heavy-load open gears are a common transmission mode. Open gears are widely used in various types of large equipment such as granulators, drum pulpers and tube mills. In the actual operation process, due to the high roughness of the tooth surface, high or low operating temperature, and high operating load, it is very easy to cause friction and wear. Gear wear not only affects the progress of the work process, but also causes huge economic losses. Therefore, in order to meet the harsh use conditions, reduce mechanical friction and wear, and extend the service life of the machinery, it is necessary to use grease reasonably and prepare suitable grease to meet the actual use needs.
[0003] Graphene is often used as a component of grease. Graphene is an atom-thick sheet of carbon atoms arranged in a hexagonal lattice structure. Since its invention in 2004, it has become the most promising material. Graphene has high electrical and thermal conductivity, excellent mechanical strength and large specific surface area. It can be used to improve the wear resistance of grease and reduce the friction of the gear running contact surface. However, since graphene is prone to aggregation and poor dispersion in the process of preparing grease, it ultimately leads to poor lubrication and wear resistance of the grease. Therefore, a large number of methods for modifying graphene have emerged. Patent CN202110423727.0 discloses a method for preparing a super-regular graphene-based grease, in which graphite powder is subjected to oxidation and high-temperature reduction processes, and super-regular graphene sheets are used in grease by dissolution-evaporation-macroscopic dispersion-microscopic homogenization. The friction coefficient of the grease is small, and the friction coefficient tends to be stable with increasing friction time.
[0004] Patent CN202010819805.4 discloses a method for preparing graphene using a composite ionic liquid, wherein the graphite powder after grinding pretreatment is mixed with the composite ionic liquid, and carbon dioxide is used as a protective gas for reaction, and the dispersion of graphene is stabilized by the Coulomb effect between anions and cations, and the graphene has good dispersibility. However, as an organic salt, ionic liquid has poor anti-wear performance and extreme pressure properties when used alone, so it needs to be used in combination with nanomaterials or solid films.
[0005] Patent 202211692907.X discloses a grease for a harmonic reducer and a preparation method thereof. The polyhydrogenated styrene / isoprene type improver and the polyisobutylene type structure improver in the grease improve the adhesion, and the use of organic molybdenum with zinc salt and thiadiazole improves the extreme pressure properties of the grease.
[0006] In the preparation process of grease, in addition to its anti-friction property and the problem of coping with high-pressure use, the service life of the grease also needs to be considered. One of the important evaluation indicators is the dropping point and working cone penetration of the grease. Patent CN201410026925.3 discloses a food-grade grease composition and a preparation method thereof. The combined grease is prepared using base oil, benzoic acid, aluminum isopropoxide trimer, rust inhibitor and silicone oil as raw materials. The working cone penetration of the grease is 270-280 (0.1mm) and the dropping point is in the range of 298-305℃.
[0007] As an important evaluation index, high oil separation and large evaporation loss of grease will directly affect the normal use of grease. Patent CN201310084582.1 discloses a high-performance composite calcium sulfonate-based grease and its preparation method. The composite calcium sulfonate-based grease prepared from high-base calcium sulfonate, base oil, lauric acid, low molecular alcohol, high-purity water, boric acid, calcium hydroxide, antioxidant and HL-functional agent has the advantages of low oil separation, high temperature resistance, extreme pressure and anti-wear properties.
[0008] The grease with good oxidation stability can be used for a long time and has stable properties. Patent 201911307265.5 discloses a method for preparing graphene composite grease, which uses base oil, graphene, polymer acid, calcium hydroxide, low molecular weight acid, lithium hydroxide, etc. as raw materials, and lithium-based grease is prepared by adding raw materials in batches. The obtained grease has good colloidal stability, high dropping point, friction reduction performance and oxidation resistance, which prolongs the service life of the grease.
[0009] Although certain progress has been made in the research of grease, in the preparation process of graphene grease for heavy-loaded open gears, the lubrication and wear resistance, extreme pressure, dropping point, cone penetration, oil separation, evaporation loss and oxidation stability of the grease need to be comprehensively considered.
[0010] Therefore, a heavy-load open gear graphene grease and a preparation method thereof are proposed. Summary of the invention
[0011] The object of the present invention is to provide a heavy-load open gear graphene grease and a preparation method thereof. The graphene oxide is modified, and the modified graphene obtained has a synergistic effect with nano-tungsten disulfide in an additive, and the obtained heavy-load open gear graphene grease has an average wear spot diameter of 0.296-0.491 mm and a friction coefficient of 0.02-0.09; the modified graphene is obtained by synthesizing anionic salts, and is connected to the surface of the graphene oxide through chemical bonds, and the modified graphene has a synergistic effect with dibutyl dithiocarbamate oxymolybdenum and 2-mercapto-1,3,4-thiadiazole in the additive, and the obtained heavy-load open gear graphene grease P is obtained. BThe values are 1236N and 1569N, P D The values are 6080N and 7846N; Epoxy Jatropha Oil is obtained by oxidizing Jatropha Oil, the epoxy Jatropha Oil is ring-opened to react with the carboxyl group in the amino polyethylene glycol carboxyl solution, and the unreacted amino group in the amino polyethylene glycol carboxyl is covalently bonded with phytic acid to further prepare modified graphene and heavy-load open gear graphene grease; Fumed silica is used as a thickener for synthesizing grease, and the amount of phytic acid and 2-hydroxy-3-naphthoic acid, the specific surface area of fumed silica and the pH of the system are controlled to obtain a heavy-load open gear graphene grease with a cone penetration of 355-430 (0.1 mm) and a dropping point of 220-32 9℃; using modified graphene, PAO, alkyl naphthalene base oil, fumed silica and additives as raw materials to prepare grease, by changing the addition amount of PAO, alkyl naphthalene base oil, fumed silica and modified graphene, the initial oxidation temperature of the heavy-duty open gear graphene grease obtained is 280℃-295℃, and the low-temperature similar viscosity at -40℃ is 796-980Pa·s; changing the preparation method of the ionic liquid in the modified graphene, changing the mass ratio of the surfactant to the modified graphene intermediate II and the modified jatropha oil, and by adding the PAO reaction raw materials in batches, the addition amount of the first raw material is lower than the addition amount of the second raw material. The final grease steel mesh oil separation amount is 0.13%-0.27%, and the evaporation loss is 0.08%-0.33%.
[0012] To achieve the above object, the present invention provides the following technical solutions:
[0013] On the one hand, the present invention provides a method for preparing a heavy-load open gear graphene grease, characterized in that it comprises the following steps:
[0014] Oxidizing graphite powder to obtain graphene oxide; adding 0.16-0.38 parts of octadecylamine, 1-hydroxybenzotriazole, 4-dimethylaminopyridine, 0.09-0.22 parts of trimethylsilyl chloride, DMF and hydrochloric acid to a mixture of the graphene oxide and water to obtain a modified graphene precursor; adding 0-0.21 parts of 1-methylimidazole to the modified graphene precursor to react to obtain a modified graphene intermediate 1; adding 0-1.35 parts of anionic salt to the modified graphene intermediate 1, and refluxing to obtain a modified graphene intermediate 2;
[0015] Adding NH2-PEG-COOH solution to epoxidized jatropha oil to obtain NH2-PEG-COOH-JCOE solution; the amount of NH2-PEG-COOH solution added is 10.9-28.2 parts; adding 594-627 parts of phytic acid solution after heating, and performing vacuum distillation after reaction to obtain modified jatropha oil;
[0016] Sodium dodecylbenzene sulfonate, Tween 80, the modified graphene intermediate 2, and the modified jatropha curcas oil in a mass ratio of 0.01-0.03:0.01-0.02:1:0.3 are placed in a ball mill to grind to obtain modified graphene;
[0017] A mixture of PAO and 0-83 parts of alkyl naphthalene oil is used to obtain a mixed base oil; the PAO is 1 / 20-4 / 5 of the total added amount of PAO; after the temperature is raised to react, the modified graphene and 7.21-9.01 parts of a specific surface area of 100-300m 2 / g of thickener, the pH of the system is 3.0-5.0, and the temperature is increased to react to obtain a heavy-load open gear graphene grease precursor; the PAO, stearic acid and modified graphene are added, the temperature is increased to react, the temperature is lowered, additives are added, and the heavy-load open gear graphene grease is obtained by grinding; the total amount of the modified graphene added is 0.05-0.40 parts; the total amount of the PAO added is 0-83.0 parts; the grinding speed is 250-400rpm, and the grinding time is 1.5-3.5h.
[0018] Preferably, the preparation method of the graphene oxide is as follows: concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 4:1 to obtain a mixed acid solution; 10.5 parts of the graphite powder and 8.0 parts of sodium nitrate are added to 0.7L of the mixed acid solution, and ultrasonically reacted for 2 hours to obtain a graphene oxide solution; the graphene oxide solution is centrifuged to obtain an insoluble matter; the insoluble matter is washed with a hydrogen peroxide solution with a volume fraction of 30% and a hydrochloric acid solution with a volume fraction of 5%, and then repeatedly washed with deionized water, and dried to obtain graphene oxide.
[0019] Preferably, the anion salt is one of potassium hexafluorophosphate and 2-hydroxy-3-naphthoic acid borate; the preparation method of the 2-hydroxy-3-naphthoic acid borate comprises the following steps:
[0020] Dispersing 0.76-1.15 parts of 2-hydroxy-3-naphthoic acid in 20 parts of DMF to obtain a 2-hydroxy-3-naphthoic acid solution; dispersing 0.30 parts of boric acid in 10 parts of DMF to obtain an inorganic acid solution; adding the inorganic acid solution to the 2-hydroxy-3-naphthoic acid solution, and then adding 0.02 parts of lithium carbonate, slowly raising the temperature to 30-60°C, reflux reacting until the pH value of the system is stable, and obtaining a product; the product is centrifuged, washed and dried to obtain the 2-hydroxy-3-naphthoic acid borate.
[0021] Preferably, the preparation method of the modified jatropha oil is as follows: add jatropha oil to a three-necked flask, add glacial acetic acid and concentrated sulfuric acid thereto under rapid stirring, mix well and heat to 30°C to obtain jatropha oil to be oxidized; add hydrogen peroxide with a mass fraction of 35% to the jatropha oil to be oxidized at a rate of 2 drops per second, heat to 65°C and react for 4.5 hours, separate and wash to obtain the epoxidized jatropha oil; add 1 / 3 of the NH2-PEG-COOH solution to the epoxidized jatropha oil, react at 600 rpm for 6 hours, and then continue to add 2 / 3 of the amino polyethylene glycol carboxyl The invention discloses a method for preparing a modified jatropha oil solution comprising: preparing a NH2-PEG-COOH-JCOE solution and reacting the solution for 15 hours to obtain an amino-polyethylene glycol carboxyl grafted epoxidized jatropha oil solution (NH2-PEG-COOH-JCOE); wherein the total amount of the amino-polyethylene glycol carboxyl solution added is 10.9-28.2 parts; heating the NH2-PEG-COOH-JCOE solution to 75°C, slowly adding 594-627 parts of a phytic acid solution thereto, and reacting the solution for 24 hours to obtain a PTE-NH2-PEG-COOH-JCOE solution; removing moisture from the PTE-NH2-PEG-COOH-JCOE solution by vacuum distillation, adding 5 parts of magnesium sulfate, and drying the solution for 12 hours to obtain the modified jatropha oil.
[0022] Preferably, the preparation method of the heavy-duty open gear graphene grease is as follows: add the dodecyl hydroxystearic acid and the stearic acid and 0-83 parts of the alkyl naphthalene oil to the PAO to obtain a mixed base oil; the first addition amount of the PAO is 1 / 20-4 / 5 of the total addition amount of the PAO; the mixed base oil is heated to 90°C and maintained for 1 hour, and then 1 / 4 of the modified graphene and 7.21-9.01 parts of the specific surface area of 100-300m 2 / g of the thickener, adjusting the pH of the system to 3.0-5.0, raising the temperature to 120°C, reacting for 2h to obtain the heavy-load open gear graphene grease precursor; adding the PAO to the heavy-load open gear graphene grease precursor, supplementing the stearic acid, and then adding 3 / 4 of the modified graphene, raising the temperature to 200°C, reacting for 20min, stopping heating and stirring, and when the temperature drops to 70°C, adding the additives thereto, stirring and mixing for 1h, and cooling to room temperature to obtain a heavy-load open gear graphene grease precursor; Gear graphene grease intermediate; the second addition amount of the PAO is 1 / 5-19 / 20 of the total addition amount of PAO by mass; the heavy-load open gear graphene grease intermediate is placed in a three-roll grinder, the grinding speed is 250-400rpm, the grinding time is 1.5-3.5h, and the heavy-load open gear graphene grease is obtained; the total addition amount of the PAO is 0-83.0 parts; the total addition amount of the modified graphene is 0.05-0.40 parts; the thickener is fumed silica.
[0023] Preferably, the 1-methylimidazole is 0.05-0.10 parts; the anion salt is 0.55-1.35 parts; and the alkyl naphthalene base oil is 23-30 parts.
[0024] Preferably, the first addition amount of PAO is 1 / 20-2 / 5 of the total addition amount of PAO by mass; the second addition amount of PAO is 3 / 5-19 / 20 of the total addition amount of PAO by mass.
[0025] Preferably, the additive includes 0.1 parts of nano-metal sulfide, 0.01-0.03 parts of dibutyl dithiocarbamate oxymolybdenum, 0.01-0.04 parts of 2-mercapto-1,3,4-thiadiazole, 0.03 parts of trans-1,2-cyclohexanedicarboxylic acid, and 0.02 parts of 2,5-2-mercapto-1,3,4-thiadiazole dimer.
[0026] Preferably, the nano-metal sulfide is one of nano-tungsten disulfide and nano-molybdenum disulfide; the particle size of the nano-tungsten disulfide is 500 μm; the particle size of the nano-molybdenum disulfide is 500 μm.
[0027] On the other hand, the present invention provides a heavy-load open gear graphene grease, characterized in that: the heavy-load open gear graphene grease comprises the modified graphene, the PAO, the alkyl naphthalene oil, the dodecahydroxystearic acid, the stearic acid, and the additive; the heavy-load open gear graphene grease is prepared by any one of the preparation methods described above; the heavy-load open gear graphene grease has an average wear spot diameter of 0.296-0.491 mm and a friction coefficient of 0.02-0.09; the heavy-load open gear graphene grease P B The values are 1236N and 1569N, P D The values are 6080N and 7846N; the cone penetration of the heavy-load open gear graphene grease is 355-430 (0.1mm), and the dropping point is 220-329°C; the initial oxidation temperature of the heavy-load open gear graphene grease is 280°C-295°C, and the low-temperature similar viscosity at -40°C is 796-980Pa·s; the steel mesh oil separation of the heavy-load open gear graphene grease is 0.13%-0.27%, and the evaporation loss is 0.08%-0.33%.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention chemically modifies graphene, and grafts octadecylamine and ionic liquid on the graphene surface. The carboxyl group on the graphene surface is covalently connected to the amino group of octadecylamine through a chemical bond, and a long-chain alkane is introduced into the system. The long carbon chain provides more intermolecular contact points, and the friction between molecules is improved, and the friction stress is enhanced; the carboxyl group on the graphene surface is first coupled with trimethylchlorosilane after hydrolysis, and then the chlorine element is replaced by 1-methylimidazole to form imidazole cations and chloride ions, and the chloride ions are replaced by potassium hexafluorophosphate. Imidazole and graphene interact through Π-Π conjugation, and an ionic liquid film is formed on the surface of graphene, and a chemical deposition film with Fe2O3 and Fe3O4 as the main components is also formed. Modified graphene is obtained by controlling the amount of the modified substance, and the modified graphene has good dispersibility, and the modified graphene and nano-tungsten disulfide synergistically reduce the friction between heavy-load open gears. The obtained heavy-load open gear graphene grease has an average wear spot diameter of 0.296-0.491 mm, a friction coefficient of 0.02-0.09, and good lubrication and wear resistance.
[0030] 2. Synthesize anionic salts with 2-hydroxy-3-naphthoic acid and boric acid as raw materials, and use them to modify graphene to finally prepare lubricating grease. Control the amount of raw materials, the amount of additives, the grinding speed and grinding time of the lubricating grease to obtain lubricating grease P B The values are 1236N and 1569N, P D The values are 6080N and 7846N, and the extreme pressure performance of the grease is good. The extreme pressure performance of the grease is improved by forming a borate film between the grease and the open gear, and the additives dibutyl dithiocarbamate oxymolybdenum and 2-mercapto-1,3,4-thiadiazole work together.
[0031] 3. The jatropha oil is oxidized to obtain epoxy jatropha oil, and the epoxy jatropha oil is ring-opened to react with the carboxyl group in the amino polyethylene glycol carboxyl solution. The unreacted amino group in the amino polyethylene glycol carboxyl is then covalently linked to phytic acid to further prepare modified graphene and grease. The amount of phytic acid in the modified jatropha oil is controlled, and the amount of 2-hydroxy-3-naphthoic acid in 2-hydroxy-3-naphthoic acid borate is changed to obtain modified graphene. The modified graphene is then mixed with base oil, fumed silica and additives to obtain grease. The hydroxyl groups on the surface of the fumed silica can form intermolecular hydrogen bonds with the hydroxyl groups on the surface of the graphene, and the specific surface area of the fumed silica is controlled to be 100-300m 2 / g range, and the pH of the system is controlled. The cone penetration of the obtained grease is in the range of 355-430 (0.1mm), and the dropping point is in the range of 220-329°C. The grease has good physical and chemical properties and can meet the actual high-temperature use requirements.
[0032] 4. Grease is prepared with modified graphene, PAO, alkylnaphthalene base oil, fumed silica and additives as raw materials. By changing the addition amount of PAO, alkylnaphthalene base oil and fumed silica, the initial oxidation temperature of the heavy-duty open gear graphene grease obtained is 280°C-295°C, and the low-temperature similar viscosity at -40°C is 796-980Pa·s. Alkylnaphthalene has the function of improving the compatibility of auxiliary materials with the system, and has excellent oxidation stability. The electron-rich naphthalene ring in alkylnaphthalene can capture the oxidizing groups generated by the oxidation of hydrocarbon groups, making it difficult for the entire oxidation chain to form, thereby preventing the oxidation process; in addition, alkylnaphthalene and fumed silica have good low-temperature resistance. Therefore, the grease prepared by the present invention has good low-temperature resistance and oxidation stability.
[0033] 5. By changing the preparation method of the ionic liquid in the modified graphene, changing the mass ratio of the surfactant to the modified graphene intermediate II and the modified jatropha oil, and by adding the PAO reaction raw materials in batches, the amount of the first raw material added is lower than the amount of the second raw material added. The final grease steel mesh oil separation is 0.13%-0.27%, and the evaporation loss is 0.08%-0.33%. The addition of ionic liquid reduces the evaporation loss of the grease; the two surfactants sodium dodecylbenzene sulfonate and Tween 80 promote the close connection between the modified graphene intermediate II and the modified jatropha oil, and at the same time increase the compatibility of the obtained modified graphene with components such as base oil. Sodium dodecylbenzene sulfonate, as an ionic surfactant, improves the compatibility of imidazole and 2-hydroxy-3-naphthoic acid borate in the ionic liquid on the surface of the modified graphene with the system. The surfactant, modified graphene and base oil are used reasonably, which reduces the oil separation of the grease and the evaporation loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a graph showing the test results of the average wear spot diameter and friction coefficient of the grease obtained in Example 17 of the present invention;
[0035] Figure 2 This is a graph showing the test results of oil separation and evaporation loss of the grease steel mesh obtained in Example 63 of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] See also Figure 1 to Figure 2The present invention provides a heavy-load open gear graphene grease and a preparation method thereof, and the technical scheme is as follows:
[0038] The substance information involved in the present invention is as follows:
[0039] Jatropha curcas oil, industrial grade, was purchased from Jiangxi Zhonghuan New Materials Co., Ltd.;
[0040] Aminopolyethylene glycol carboxyl was purchased from Guangzhou Carbon Technology Co., Ltd.;
[0041] Phytic acid was purchased from Laiyang Wanjiwei Bioengineering Co., Ltd.;
[0042] 2-Mercapto-1,3,4-thiadiazole was purchased from Hangzhou Shitean Chemical Co., Ltd.;
[0043] SYP grease anti-wear and extreme pressure performance tester was purchased from Shanghai Mitong Electromechanical Technology Co., Ltd.;
[0044] The grease cone penetration tester was purchased from Changzhou Dedu Precision Instrument Co., Ltd.
[0045] SYS-3498-Lubricating grease wide temperature range dropping point tester was purchased from Dandong Zhongyi Electronic Equipment Co., Ltd.;
[0046] High-viscosity polyalphaolefin (PAO) and alkyl naphthalene base oils were purchased from ExxonMobil;
[0047] Nano-tungsten disulfide, 500 nm; Molybdenum disulfide, 500 nm, were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.
[0048] Dibutyl dithiocarbamate oxymolybdenum was purchased from Hangzhou Shitean Chemical Co., Ltd.;
[0049] 2-Mercapto-1,3,4-thiadiazole was purchased from Hunan Yunbang Biotechnology Co., Ltd.;
[0050] 2,5-2-Mercapto-1,3,4-thiadiazole dimer CAS: 72676-55-2; Octadecylamine CAS: 124-30-1; 1-Hydroxybenzotriazole CAS: 2592-95-2; 4-Dimethylaminopyridine CAS: 1122-58-3; 2-Hydroxy-3-naphthoic acid CAS: 202-180-8; Trimethylchlorosilane CAS: 75-77-4; 1-Methylimidazole CAS: 616-47-7; Potassium hexafluorophosphate CAS: 17084-13-8; Trans-1,2-cyclohexanedicarboxylic acid CAS: 2305-32-0; Dodecylhydroxystearic acid CAS: 106-14-9.
[0051] SYS-3498-Lubricating grease wide temperature range dropping point tester was purchased from Dandong Zhongyi Electronic Equipment Co., Ltd.
[0052] It should be noted that the other chemical reagents, consumables and instruments in the present invention are all reagents, consumables and instruments commonly used in chemical experiments; the purity of the chemical reagents is analytical grade.
[0053] Examples 1-12
[0054] Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 4:1 to obtain a mixed acid solution; 10.5 parts of graphite powder and 8.0 parts of sodium nitrate are added to 0.7L of the mixed acid solution, and ultrasonically reacted for 2 hours to obtain a graphene oxide solution; the graphene oxide solution is centrifuged to obtain an insoluble matter; the insoluble matter is washed with a 30% by volume hydrogen peroxide solution and a 5% by volume hydrochloric acid solution, and then repeatedly washed with deionized water, and dried to obtain graphene oxide;
[0055] The graphene oxide is mixed with 300 parts of deionized water to obtain a graphene mixed solution; 0.19 parts of octadecylamine, 0.23 parts of 1-hydroxybenzotriazole, 0.19 parts of 4-dimethylaminopyridine, 0.20 parts of trimethylsilyl chloride, 20 parts of DMF and 5 parts of hydrochloric acid with a volume fraction of 30% are added to the graphene mixed solution, and under nitrogen protection, reflux reaction is carried out at 120° C. for 12 hours to obtain a modified graphene precursor; 0.10 parts of 1-methylimidazole are added to the modified graphene precursor, and the reflux reaction is continued for 24 hours to obtain a modified graphene intermediate 1; 1.20 parts of anionic salt potassium hexafluorophosphate are added to the modified graphene intermediate 1, and reflux for 12 hours, and the obtained precipitate is centrifuged, washed with deionized water, and dried to obtain a modified graphene intermediate 2;
[0056] 200 parts of jatropha curcas oil were added to a three-necked flask, and 1 part of glacial acetic acid and 2 parts of concentrated sulfuric acid were added thereto under rapid stirring, and the mixture was evenly mixed and then heated to 30° C. to obtain the jatropha curcas oil to be oxidized; 50 parts of 35% hydrogen peroxide were added to the jatropha curcas oil to be oxidized at a rate of 2 drops / s, and the mixture was heated to 65° C. and reacted for 4.5 hours, and the epoxidized jatropha curcas oil was obtained after separation and washing; 1 / 3 volume of aminopolyethylene glycol carboxyl solution was added to the epoxidized jatropha curcas oil, and the reaction was continued at 600 rpm for 6 hours, and then 2 / 3 volume of the aminopolyethylene glycol carboxyl solution was added, and the reaction was continued. After 15 hours, an amino polyethylene glycol carboxyl grafted epoxidized jatropha oil solution (NH2-PEG-COOH-JCOE) is obtained; the total amount of the amino polyethylene glycol carboxyl solution added is 19.1 parts; the NH2-PEG-COOH-JCOE solution is heated to 75°C, 605 parts of phytic acid (PTE) solution are slowly added thereto, and the PTE-NH2-PEG-COOH-JCOE solution is obtained after reacting for 24 hours; the PTE-NH2-PEG-COOH-JCOE solution is subjected to reduced pressure distillation to remove water, 5 parts of magnesium sulfate are added, and dried for 12 hours to obtain modified jatropha oil;
[0057] Sodium dodecylbenzene sulfonate, Tween 80, modified graphene intermediate II, and modified jatropha curcas oil in a mass ratio of 0.01:0.01:1:0.3 are placed in a ball mill for grinding to obtain modified graphene; the grinding conditions are as follows: the ball-to-material mass ratio is 50:1, the grinding revolution speed is 300 rpm, and the forward and reverse rotations are 2 hours each;
[0058] 6.5 parts of dodecyl stearic acid, 2.1 parts of stearic acid and 23 parts of alkyl naphthalene base oil were added to 1 / 4 PAO to obtain a mixed base oil; the mixed base oil was heated to 90° C. and maintained for 1 hour, and then 1 / 4 modified graphene and 7.51 parts of a specific surface area of 300 m 2 / g of fumed silica (thickener), adjust the pH of the system to 5.0, raise the temperature to 120°C, react for 2h to obtain a heavy-load open gear graphene grease precursor; add 3 / 4 PAO as a heating oil to the heavy-load open gear graphene grease precursor, add 0.6 parts of stearic acid, then add 3 / 4 modified graphene, raise the temperature to 200°C, stop heating and stirring after reacting for 20min, add additives when the temperature drops to 70°C, stir and mix for 1h, and cool to room temperature to obtain a heavy-load open gear graphene grease intermediate; place the heavy-load open gear graphene grease intermediate in a three-roll mill, grind at a speed of 300rpm, and grind for 3h to obtain a heavy-load open gear graphene grease; the total amount of PAO added is 60 parts; the total amount of modified graphene added is 0.1 parts;
[0059] The additives include 0.1 parts of nano tungsten disulfide, 0.03 parts of dibutyl dithiocarbamate oxymolybdenum, 0.01 parts of 2-mercapto-1,3,4-thiadiazole, 0.03 parts of trans-1,2-cyclohexanedicarboxylic acid, and 0.02 parts of 2,5-2-mercapto-1,3,4-thiadiazole dimer; the total addition amount of the PAO, the alkyl naphthalene base oil, the dodecyl stearic acid, the stearic acid, the modified graphene, the thickener and the additives is 100 parts.
[0060] Different from Example 1, the following preparation method is changed, as shown in Table 1.
[0061] Table 1 Specific changes in the preparation method
[0062]
[0063]
[0064] Comparative Example 4
[0065] The difference from Example 3 is that the nano tungsten disulfide is replaced by nano molybdenum disulfide.
[0066] Examples 13-16
[0067] Different from Example 3, the added amounts of modified graphene are 0.05 parts, 0.08 parts, 0.13 parts and 0.20 parts respectively.
[0068] Embodiment 17
[0069] The heavy-duty open gear graphene grease prepared in Examples 1-16 and Comparative Examples 1-4 was subjected to anti-wear performance test. The test method was carried out in accordance with SH / T0204-1992 "Determination of Anti-wear Performance of Grease (Four-ball Machine Method)". The test conditions were as follows: test temperature 76°C, spindle speed 1200rpm, test load 392N, test time 60min. The final test results are shown in Table 2. The test results of the grease in Examples 1-7 Figure 1 shown.
[0070] Table 2 Test results of anti-wear properties of lubricating greases of Examples 1-16 and Comparative Examples 1-4
[0071]
[0072]
[0073] As shown in Table 2 and Figure 1As shown, the average wear spot diameter of the heavy-duty open gear graphene grease prepared in the embodiment of the present invention is 0.296-0.491 mm, and the friction coefficient is 0.02-0.09. In Examples 1-7, by changing the addition amount of octadecylamine, trimethylchlorosilane, 1-methylimidazole and potassium hexafluorophosphate, the average wear spot diameter shows a trend of decreasing, increasing and decreasing, and the average friction coefficient reaches the minimum value in Example 3. The surface of graphene oxide is rich in hydroxyl and carboxyl groups, and some carboxyl groups are covalently connected to the amino group of octadecylamine through chemical bonds. Long-chain alkanes are introduced into the system, and long carbon chains provide more intermolecular contact points, thereby increasing the friction between molecules. When the gear is rotated, the direct force of the gear is converted into the friction inside the grease, reducing the friction between the gears; some carboxyl groups are first coupled with trimethylchlorosilane after hydrolysis, and then the chlorine element is replaced by 1-methylimidazole to form imidazole cations and chloride ions, and the chloride ions are replaced by potassium hexafluorophosphate. Imidazole and graphene interact through Π-Π conjugation, and the formed ionic liquid forms a film on the surface of graphene, and cooperates with nano-tungsten disulfide to interact with the engineering surface under the action of friction stress, which not only protects the surface and improves the surface strength, but also reduces friction and promotes the dispersion of modified graphene in grease. Comparative Example 1 and Comparative Example 2 do not add octadecylamine, 1-methylimidazole, and potassium hexafluorophosphate, respectively, so the friction coefficient is large compared with the embodiment, and the average wear spot diameter is large. In comparative example 4, after nano-tungsten disulfide is replaced by nano-molybdenum disulfide, the lubrication performance and friction resistance of the grease decrease. The results of Example 3 are compared with those of Examples 8-12. As the relative molecular mass of the aminopolyethylene glycol carboxyl group increases, the wear spot diameter and the friction coefficient first reach the optimal value, and then increase to varying degrees. As shown in Example 3, when the relative molecular mass of the aminopolyethylene glycol carboxyl group is 10,000, the friction and abrasion resistance are the best. In comparative example 3, NH2-PEG-COOH-10000 is replaced by PEG200, and the final performance decreases. After mechanical grinding, the modified jatropha curcas oil is distributed inside the lamellar graphene and outside the graphene grafted octadecylamine and ionic liquid, which together improves the lubrication performance of the grease.
[0074] Comparing the results of Examples 3 and 13-16, it can be seen that when the amount of modified graphene added is 0.1 parts, that is, 0.1wt% in the system, the average wear spot diameter and friction coefficient are the smallest. During the operation of heavy-load open gears, the grease forms a chemical deposition film with Fe2O3 and Fe3O4 as the main components and a physical adsorption film rich in graphene on the friction surface. The layered structure of graphene dissociates along the interlayer during the friction process and is distributed in the depressions of the gear friction surface. At the same time, the modified jatropha oil, octadecylamine and ionic liquid on the neutralization surface work synergistically to isolate the friction surface, and continuously adsorb and desorb during the friction process, in a state of dynamic equilibrium. In summary, the grease prepared by the present invention has good lubricity and wear resistance.
[0075] Embodiment 18
[0076] Dispersing 0.76 parts of 2-hydroxy-3-naphthoic acid in 20 parts of DMF to obtain a 2-hydroxy-3-naphthoic acid solution; dispersing 0.30 parts of boric acid in 10 parts of DMF to obtain a boric acid solution; adding the boric acid solution to the 2-hydroxy-3-naphthoic acid solution, and then adding 0.02 parts of lithium carbonate, slowly raising the temperature to 50° C., and reflux reaction until the pH value of the system is stable to obtain a product; the product is centrifuged, washed and dried to obtain an anionic salt, i.e., 2-hydroxy-3-naphthoic acid borate;
[0077] Replacing 1.01 parts of potassium hexafluorophosphate with the 2-hydroxy-3-naphthoic acid borate, and then preparing the modified graphene according to the preparation method of Example 3;
[0078] 6.5 parts of dodecyl stearic acid, 2.1 parts of stearic acid and 23 parts of alkyl naphthalene base oil were added to 1 / 4 PAO to obtain a mixed base oil; the mixed base oil was heated to 90° C. and maintained for 1 hour, and then 1 / 4 modified graphene and 7.51 parts of a specific surface area of 300 m 2 / g of fumed silica (thickener), adjust the pH of the system to 5.0, raise the temperature to 120°C, react for 2h to obtain a heavy-load open gear graphene grease precursor; add 3 / 4 PAO as a heating oil to the heavy-load open gear graphene grease precursor, add 0.6 parts of stearic acid, then add 3 / 4 modified graphene, raise the temperature to 200°C, stop heating and stirring after reacting for 20min, add additives when the temperature drops to 70°C, stir and mix for 1h, and cool to room temperature to obtain a heavy-load open gear graphene grease intermediate; place the heavy-load open gear graphene grease intermediate in a three-roll mill, grind at a speed of 300rpm, and grind for 3h to obtain a heavy-load open gear graphene grease; the total amount of PAO added is 60 parts; the total amount of modified graphene added is 0.1 parts;
[0079] The additives include 0.1 parts of nano tungsten disulfide, 0.03 parts of dibutyl dithiocarbamate oxymolybdenum, 0.01 parts of 2-mercapto-1,3,4-thiadiazole, 0.03 parts of trans-1,2-cyclohexanedicarboxylic acid, and 0.02 parts of 2,5-2-mercapto-1,3,4-thiadiazole dimer; the total addition amount of the PAO, the alkyl naphthalene base oil, the dodecyl stearic acid, the stearic acid, the modified graphene, the thickener and the additives is 100 parts.
[0080] The detailed preparation methods of Examples 19-29 are listed in Table 3.
[0081] Table 3 Preparation method of lubricating grease of Examples 19-29
[0082]
[0083]
[0084] Comparative Example 5
[0085] The difference from Example 18 is that boric acid is replaced by phosphoric acid.
[0086] Comparative Example 6
[0087] Unlike Example 18, the temperature was slowly raised to 100°C.
[0088] Embodiment 30
[0089] The greases prepared in Examples 18-29 and Comparative Examples 5 and 6 were subjected to extreme pressure performance tests. The extreme pressure performance of the grease was tested in accordance with SH / T0202-92 "Test Method for Extreme Pressure Performance of Grease (Four-Ball Machine Method)" and was tested using a SYP grease anti-wear and extreme pressure performance tester; the data of the maximum non-seizure load PB and the sintering load PD are recorded in Table 4.
[0090] Grease P prepared in Example B The values are 1236N and 1569N, P D The values are 6080N and 7846N. In Examples 18-23, the amount of 2-hydroxy-3-naphthoic acid added is controlled, and the maximum no-seizure load and sintering load obtained are high, and the extreme pressure performance is good. D The highest value is 7846N. Using 2-hydroxy-3-naphthoic acid and boric acid as raw materials, borate is formed under the action of a catalyst, and then borate replaces the chloride ions on the surface of graphene to form graphene modified with borate. Borate and imidazole are closely connected with graphene through conjugation, and the friction surface forms an electric charge during movement. The charged ion particles of borate in the grease move from one side of the surface to the other, forming a borate film, which improves the extreme pressure of the final grease. When boric acid is replaced with phosphoric acid, as shown in Comparative Example 5, P B Value and P D The results of Example 21, Example 24 and Example 25 show that the extreme pressure performance of the grease is good when the reaction temperature is controlled in the range of 30-60°C. B Value and P DThe values are the lowest compared with those in the examples, which are 618N and 3089N respectively. When the temperature is too high, 2-hydroxy-3-naphthoic acid and boric acid have not reacted yet, DMF has evaporated, the raw materials form a precipitate, and the subsequent condensed DMF dissolves part of the raw materials, but the final reaction is incomplete, so the extreme pressure properties of the obtained grease decrease. The results of Examples 21, 26-29 show that the grinding revolution speed is controlled in the range of 250-400rpm, the forward and reverse rotation times are controlled in the range of 2.0-3.5h, and the addition amounts of the extreme pressure and wear-resistant agents dibutyl dithiocarbamate oxymolybdenum and 2-mercapto-1,3,4-thiadiazole in the additives are controlled in the range of 0.01-0.03 parts and 0.01-0.04 parts, respectively, and the obtained grease has good extreme pressure properties.
[0091] Table 4 Extreme pressure performance test results of lubricating greases of Examples 18-29 and Comparative Examples 5 and 6
[0092] Group <![CDATA[P B (N)]]> <![CDATA[P D (N)]]> Embodiment 18 1236 6080 Embodiment 19 1236 6080 Embodiment 20 1569 6080 Embodiment 21 1569 7846 Embodiment 22 1569 6080 Embodiment 23 1236 6080 Embodiment 24 1236 6080 Embodiment 25 1569 6080 Embodiment 26 1236 6080 Embodiment 27 1569 6080 Embodiment 28 1569 6080 Embodiment 29 1569 6080 Comparative Example 5 981 4904 Comparative Example 6 618 3089
[0093] Embodiment 31
[0094] Graphene oxide was prepared by the method of Example 1;
[0095] The graphene oxide is mixed with 300 parts of deionized water to obtain a graphene mixed solution; 0.24 parts of octadecylamine, 0.23 parts of 1-hydroxybenzotriazole, 0.19 parts of 4-dimethylaminopyridine, 0.17 parts of trimethylchlorosilane, 20 parts of DMF and 5 parts of hydrochloric acid with a volume fraction of 30% are added to the graphene mixed solution, and under nitrogen protection, reflux reaction is carried out at 120° C. for 12 hours to obtain a modified graphene precursor; 0.09 parts of 1-methylimidazole are added to the modified graphene precursor, and the reflux reaction is continued for 24 hours to obtain a modified graphene intermediate 1; 2-hydroxy-3-naphthoic acid borate prepared in Example 18 is added to the modified graphene intermediate 1, and refluxed for 12 hours, and the obtained precipitate is centrifuged, washed with deionized water, and dried to obtain a modified graphene intermediate 2;
[0096] 200 parts of jatropha curcas oil were added to a three-necked flask, and 1 part of glacial acetic acid and 2 parts of concentrated sulfuric acid were added thereto under rapid stirring, and the mixture was evenly mixed and then heated to 30° C. to obtain the jatropha curcas oil to be oxidized; 50 parts of 35% hydrogen peroxide were added to the jatropha curcas oil to be oxidized at a rate of 2 drops / s, and the mixture was heated to 65° C. and reacted for 4.5 hours, and the epoxidized jatropha curcas oil was obtained after separation and washing; 1 / 3 volume of aminopolyethylene glycol carboxyl solution was added to the epoxidized jatropha curcas oil, and the mixture was reacted at 600 rpm for 6 hours, and then 2 / 3 volume of the aminopolyethylene glycol carboxyl solution was added, and the mixture was reacted for 15 hours. Obtaining amino polyethylene glycol carboxyl grafted epoxidized jatropha oil solution (NH2-PEG-COOH-JCOE); the total amount of the NH2-PEG-COOH-10000 solution added is 19.1 parts; the NH2-PEG-COOH-JCOE solution is heated to 75°C, 605 parts of phytic acid (PTE) solution are slowly added thereto, and the PTE-NH2-PEG-COOH-JCOE solution is obtained after reacting for 24 hours; the PTE-NH2-PEG-COOH-JCOE solution is subjected to reduced pressure distillation to remove water, 5 parts of magnesium sulfate are added, and dried for 12 hours to obtain modified jatropha oil;
[0097] Sodium dodecylbenzene sulfonate, Tween 80, modified graphene intermediate II, and modified jatropha curcas oil in a mass ratio of 0.01:0.01:1:0.3 are placed in a ball mill for grinding to obtain modified graphene;
[0098] 6.5 parts of dodecyl stearic acid, 2.1 parts of stearic acid and 23 parts of alkyl naphthalene base oil were added to 1 / 4 PAO to obtain a mixed base oil; the mixed base oil was heated to 90° C. and maintained for 1 hour, and then 1 / 4 modified graphene and 7.51 parts of a carbonyl group with a specific surface area of 100 m 2 / g of fumed silica (thickener), adjust the pH of the system to 5.0, raise the temperature to 120°C, react for 2h to obtain a heavy-load open gear graphene grease precursor; add 3 / 4 PAO as a heating oil to the heavy-load open gear graphene grease precursor, add 0.6 parts of stearic acid, then add 3 / 4 modified graphene, raise the temperature to 200°C, stop heating and stirring after reacting for 20min, add additives when the temperature drops to 70°C, stir and mix for 1h, and cool to room temperature to obtain a heavy-load open gear graphene grease intermediate; place the heavy-load open gear graphene grease intermediate in a three-roll mill, grind at a speed of 300rpm, and grind for 3h to obtain a heavy-load open gear graphene grease; the total amount of PAO added is 60 parts; the total amount of modified graphene added is 0.1 parts;
[0099] The additives include 0.1 parts of nano tungsten disulfide, 0.03 parts of dibutyl dithiocarbamate oxymolybdenum, 0.01 parts of 2-mercapto-1,3,4-thiadiazole, 0.03 parts of trans-1,2-cyclohexanedicarboxylic acid, and 0.02 parts of 2,5-2-mercapto-1,3,4-thiadiazole dimer; the total addition amount of the PAO, the alkyl naphthalene base oil, the dodecyl stearic acid, the stearic acid, the modified graphene, the thickener and the additives is 100 parts.
[0100] Examples 32-36
[0101] The 2-hydroxy-3-naphthoic acid borate prepared in Example 18 was replaced by the 2-hydroxy-3-naphthoic acid borate prepared in Examples 19, 20, 21, 22, and 23, respectively, and the other preparation methods remained consistent with Example 31.
[0102] Examples 37-39
[0103] The difference from Example 31 is that the added amounts of phytic acid solution are 601 parts, 594 parts and 627 parts respectively.
[0104] Embodiment 40, 41
[0105] The difference from Example 31 is that the specific surface areas of the fumed silica are 200 and 300 m 2 / g.
[0106] Examples 42-44
[0107] Different from Example 31, after the fumed silica was added to the system, the pH of the system was adjusted to 3.0, 4.0 and 4.5 respectively.
[0108] Embodiment 45
[0109] The heavy-duty open gear graphene grease prepared in Examples 31-44 was tested for dropping point and cone penetration. The cone penetration test method was carried out in accordance with GB / T 269-2023 "Cone penetration test method for lubricating grease and petroleum grease", the grease cone penetration tester model was WZ-269, and the test temperature was 25°C; the grease dropping point was carried out in accordance with GB / T 3498-2008 "Determination of dropping point of lubricating grease over a wide temperature range", and the dropping point of the embodiment was tested using SYS-3498-Lubricating grease wide temperature range dropping point tester. The test results are shown in Table 5.
[0110] Table 5 Cone penetration and dropping point measurement results of graphene grease of Examples 31-44.
[0111] Group Cone penetration (0.1mm) Dropping point(℃) Embodiment 31 420 220 Embodiment 32 402 245 Embodiment 33 381 263 Embodiment 34 355 296 Embodiment 35 414 311 Embodiment 36 430 318 Embodiment 37 405 323 Embodiment 38 390 326 Embodiment 39 394 329 Embodiment 40 411 304 Embodiment 41 379 309 Embodiment 42 365 279 Embodiment 43 385 260 Embodiment 44 408 323
[0112] The grease prepared by the preparation method of the present invention has a cone penetration in the range of 355-430 (0.1 mm) and a dropping point in the range of 220-329°C. In Examples 31-36, as the content of 2-hydroxy-3-naphthoic acid borate introduced into the graphene surface increases, the dropping point of the grease shows a trend of gradually increasing. The dropping point of the grease in Example 36 is the highest, at 318°C. The naphthalene rings and graphene in the 2-hydroxy-3-naphthoic acid borate improve the ability of the grease to cope with high temperatures, making it have good high temperature resistance. The cone penetration shows a trend of first decreasing and then increasing. When the 2-hydroxy-3-naphthoic acid borate introduced into graphene is excessive, the hardness of the grease is reduced and the fluidity is increased. In Examples 37-39, as phytic acid gradually increases, the cone penetration gradually decreases. When the amount of phytic acid added in Example 39 is 627 parts, the cone penetration increases slightly and the dropping point gradually increases. Phytic acid is connected to jatropha oil through aminopolyethylene glycol carboxyl, which improves the overall hardness of the grease system. At the same time, phytic acid has high temperature resistance. Phytic acid decomposes under heat to produce inositol phosphate. The presence of phosphate in the system also improves the high temperature resistance of the grease, and the dropping point of the grease is improved. The results of Examples 31, 40, and 41 show that as the specific surface area of fumed silica increases, the dropping point increases, while the cone penetration shows a trend of gradually decreasing. The silicon-oxygen bond in fumed silica gives the grease the property of high temperature resistance, but since the mass of the fumed silica added in the above embodiments is the same, the dropping point does not change significantly; and as the specific surface area of fumed silica increases, fumed silica is more likely to contact with other substances, such as the hydroxyl groups on the surface of fumed silica can form intermolecular hydrogen bonds with the hydroxyl groups on the surface of graphene, and the increase in the contact specific surface area increases the intermolecular force, reduces the fluidity of the grease, and reduces the cone penetration. The results of Examples 31 and 42-44 show that when the pH of the system is in the range of 3-5, the cone penetration and dropping point of the grease are good.
[0113] Embodiment 46
[0114] The modified graphene prepared by the method of Example 3 was used to prepare the grease. 6.5 parts of dodecyl hydroxystearic acid, 2.1 parts of stearic acid and 23 parts of alkyl naphthalene base oil were added to 1 / 4 PAO to obtain a mixed base oil; the mixed base oil was heated to 90°C and maintained for 1 hour, and then 1 / 4 modified graphene, 7.51 parts of alkyl naphthalene with a specific surface area of 300 m 2 / g of fumed silica (thickener), adjust the pH of the system to 5.0, raise the temperature to 120°C, react for 2h to obtain a heavy-load open gear graphene grease precursor; add 3 / 4 PAO as a heating oil to the heavy-load open gear graphene grease precursor, add 0.6 parts of stearic acid, then add 3 / 4 modified graphene, raise the temperature to 200°C, stop heating and stirring after reacting for 20min, add additives when the temperature drops to 70°C, stir and mix for 1h, and cool to room temperature to obtain a heavy-load open gear graphene grease intermediate; place the heavy-load open gear graphene grease intermediate in a three-roll mill, grind at a speed of 300rpm, and grind for 3h to obtain a heavy-load open gear graphene grease; the total amount of PAO added is 60 parts; the total amount of modified graphene added is 0.1 parts;
[0115] The additives include 0.1 parts of nano tungsten disulfide, 0.03 parts of dibutyl dithiocarbamate oxymolybdenum, 0.01 parts of 2-mercapto-1,3,4-thiadiazole, 0.03 parts of trans-1,2-cyclohexanedicarboxylic acid, and 0.02 parts of 2,5-2-mercapto-1,3,4-thiadiazole dimer; the total addition amount of the PAO, the alkyl naphthalene base oil, the dodecyl stearic acid, the stearic acid, the modified graphene, the thickener and the additives is 100 parts.
[0116] The detailed information of the preparation process of the embodiment is shown in Table 6.
[0117] Table 6 Changes in base oil preparation process and grease performance test results
[0118]
[0119] Embodiment 53
[0120] Different from Example 46, the total amount of modified graphene added is 0.4 parts; the amount of fumed silica added is 7.21 parts.
[0121] Effect Example 1
[0122] The lubricating greases prepared in Examples 46-53 and Comparative Examples 7 and 8 were subjected to comprehensive performance tests to determine the initial oxidation temperature and low-temperature similar viscosity of the lubricating greases. The similar viscosity was determined using a SYP-0048 lubricating grease similar viscosity tester, with reference to the method of SH / T 0048-1991 "Method for Determining Similar Viscosity of Lubricating Greases". The similar viscosity of the lubricating greases measured at -40°C is recorded in Table 6; the PDSC method was used to determine the anti-oxidation performance of the lubricating greases, and the test results were characterized by the initial oxidation temperature. The test results are shown in Table 6.
[0123] The initial oxidation temperature of the grease prepared in the embodiment of the present invention is 280°C-295°C, and the low-temperature similar viscosity at -40°C is 796-980Pa·s. In Examples 46-49, as the amount of alkylnaphthalene base oil added decreases and the amount of fumed silica added increases, the initial oxidation temperature first decreases and then increases, and the low-temperature similar viscosity gradually decreases. On the one hand, alkylnaphthalene has the function of improving the compatibility of auxiliary materials with the system, and on the other hand, it has excellent oxidation stability. The electron-rich naphthalene ring in alkylnaphthalene can capture the oxidizing groups produced by the oxidation of hydrocarbon groups, making it difficult for the entire oxidation chain to form, thereby preventing the oxidation process. Therefore, the initial oxidation temperature decreases as the content of alkylnaphthalene base oil decreases, but the fumed silica increases therewith, thereby improving the oxidation resistance of the grease. The increase in fumed silica reduces the similar viscosity of the grease at -40°C, and fumed silica improves the low-temperature resistance of the grease, reduces the resistance of the grease to mechanical shearing in a low-temperature environment, and improves the usability of the grease under low-temperature conditions. Comparison of Examples 50-52 with Example 46 shows that, with the decrease of PAO and the increase of the amount of alkyl naphthalene base oil and fumed silica, the initial oxidation temperature gradually increases and the low-temperature similar viscosity gradually decreases, indicating that the grease prepared by the present invention has stable properties under both high and low temperature conditions of use. Compared with Example 46, Example 53 increases the amount of modified graphene added, reduces the content of fumed silica, reduces the low-temperature similar viscosity of the obtained grease, and increases the initial oxidation temperature. The modified graphene and fumed silica work synergistically to improve the high temperature and low temperature resistance of the grease. Comparative Example 7 does not add alkyl naphthalene base oil, and the initial oxidation temperature is significantly lower than that of the embodiment. Comparative Example 8 does not add fumed silica, and the low-temperature similar viscosity increases, which increases the difficulty of use under low temperature conditions, the initial oxidation temperature decreases, and the oxidation stability deteriorates.
[0124] Embodiment 54
[0125] Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 4:1 to obtain a mixed acid solution; 10.5 parts of graphite powder and 8.0 parts of sodium nitrate are added to 0.7L of the mixed acid solution, and ultrasonically reacted for 2 hours to obtain a graphene oxide solution; the graphene oxide solution is centrifuged to obtain an insoluble matter; the insoluble matter is washed with a 30% by volume hydrogen peroxide solution and a 5% by volume hydrochloric acid solution, and then repeatedly washed with deionized water, and dried to obtain graphene oxide;
[0126] The graphene oxide is mixed with 300 parts of deionized water to obtain a graphene mixed solution; 0.16 parts of octadecylamine, 0.23 parts of 1-hydroxybenzotriazole, 0.19 parts of 4-dimethylaminopyridine, 0.22 parts of trimethylsilyl chloride, 20 parts of DMF and 5 parts of hydrochloric acid with a volume fraction of 30% are added to the graphene mixed solution, and under nitrogen protection, reflux reaction is carried out at 120° C. for 12 hours to obtain a modified graphene precursor; 0.12 parts of 1-methylimidazole are added to the modified graphene precursor, and the reflux reaction is continued for 24 hours to obtain a modified graphene intermediate one; 1.35 parts of 2-hydroxy-3-naphthoic acid borate prepared in Example 21 are added to the modified graphene intermediate one, and refluxed for 12 hours, and the obtained precipitate is centrifuged, washed with deionized water, and dried to obtain a modified graphene intermediate two;
[0127] Modified Jatropha curcas oil was prepared according to the method of Example 1;
[0128] Sodium dodecylbenzene sulfonate, Tween 80, modified graphene intermediate II, and modified jatropha curcas oil in a mass ratio of 0.01:0.01:1:0.3 are placed in a ball mill for grinding to obtain modified graphene;
[0129] 6.5 parts of dodecyl stearic acid, 2.1 parts of stearic acid and 23 parts of alkyl naphthalene base oil were added to 1 / 4 PAO to obtain a mixed base oil; the mixed base oil was heated to 90° C. and maintained for 1 hour, and then 1 / 4 modified graphene and 7.51 parts of a specific surface area of 300 m 2 / g of fumed silica (thickener), adjust the pH of the system to 5.0, raise the temperature to 120°C, react for 2h to obtain a heavy-load open gear graphene grease precursor; add 3 / 4 PAO as a heating oil to the heavy-load open gear graphene grease precursor, add 0.6 parts of stearic acid, then add 3 / 4 modified graphene, raise the temperature to 200°C, stop heating and stirring after reacting for 20min, add additives when the temperature drops to 70°C, stir and mix for 1h, and cool to room temperature to obtain a heavy-load open gear graphene grease intermediate; place the heavy-load open gear graphene grease intermediate in a three-roll mill, grind at a speed of 300rpm, and grind for 3h to obtain a heavy-load open gear graphene grease; the total amount of PAO added is 60 parts; the total amount of modified graphene added is 0.1 parts;
[0130] The additives include 0.1 parts of nano tungsten disulfide, 0.03 parts of dibutyl dithiocarbamate oxymolybdenum, 0.01 parts of 2-mercapto-1,3,4-thiadiazole, 0.03 parts of trans-1,2-cyclohexanedicarboxylic acid, and 0.02 parts of 2,5-2-mercapto-1,3,4-thiadiazole dimer; the total addition amount of the PAO, the alkyl naphthalene base oil, the dodecyl stearic acid, the stearic acid, the modified graphene, the thickener and the additives is 100 parts.
[0131] Embodiment 55, 56
[0132] The difference from Example 54 is that the 2-hydroxy-3-naphthoic acid borate prepared in Examples 22 and 23 is used instead.
[0133] Examples 57-59
[0134] Different from Example 54, the mass ratios of sodium dodecylbenzene sulfonate, Tween 80, modified graphene intermediate 2, and modified jatropha curcas oil are 0.03:0.01:1:0.3, 0.01:0.02:1:0.3, and 0.03:0.02:1:0.3, respectively.
[0135] Embodiment 60
[0136] The difference from Example 54 is that the amount of PAO added for the first time is 1 / 20 of its total mass, and the amount of PAO added for the second time is 19 / 20 of its total mass.
[0137] Embodiment 61
[0138] The difference from Example 54 is that the amount of PAO added for the first time is 1 / 10 of its total mass, and the amount of PAO added for the second time is 9 / 10 of its total mass.
[0139] Embodiment 62
[0140] The difference from Example 54 is that the first amount of PAO added is 2 / 5 of its total mass, and the second amount of PAO added is 3 / 5 of its total mass.
[0141] Comparative Example 9
[0142] The difference from Example 54 is that the amount of PAO added for the first time is 4 / 5 of its total mass, and the amount of PAO added for the second time is 1 / 5 of its total mass.
[0143] Comparative Example 10
[0144] The difference from Example 54 is that the amount of 2-hydroxy-3-naphthoic acid borate added is 0 parts.
[0145] Embodiment 63
[0146] The stability of the graphene grease for heavy-duty open gears prepared in Examples 54-62 and Comparative Examples 9 and 10 was tested, and the test indicators included the oil separation of the steel mesh and the evaporation loss. The oil separation of the steel mesh was determined according to SH / T 0324-92 "Determination of Oil Separation of Grease and Steel Mesh (Static Method)", with a test temperature of 30°C and a holding time of 30 hours; the evaporation loss of the grease was determined according to GB / T 7325-87 "Determination of Evaporation Loss of Grease and Lubricating Oil", with a constant temperature water bath temperature of 100°C and a test time of. The test results are as follows: Figure 2 shown.
[0147] according to Figure 2The test results of grease performance show that the oil separation of the grease steel mesh obtained in the embodiment of the present invention is 0.13%-0.27%, and the evaporation loss is 0.08%-0.33%. Among them, in Examples 54-56, as the amount of 2-hydroxy-3-naphthoic acid added increases, the evaporation loss gradually decreases. In Example 56, a slightly excessive amount of 2-hydroxy-3-naphthoic acid enters the grease with graphene, and the evaporation loss decreases, but the oil separation shows a decreasing and increasing trend. The excess 2-hydroxy-3-naphthoic acid is not covalently linked to the components in the system through chemical bonds, so the stability of the grease is reduced to a certain extent, and the oil separation increases. In Comparative Example 10, 2-hydroxy-3-naphthoic acid borate is not added, resulting in an evaporation loss lower than the evaporation loss of the grease prepared in the embodiment. The results of Examples 54 and 57-59 are compared. By changing the mass ratio of the four components of sodium dodecylbenzene sulfonate, Tween 80, modified graphene intermediate II, and modified jatropha curcas oil, the obtained grease steel mesh oil separation and evaporation loss are small, among which the grease steel mesh oil separation obtained in Example 59 is the lowest, which is 0.13%. The two surfactants of sodium dodecylbenzene sulfonate and Tween 80 promote the close connection between the modified graphene intermediate II and the modified jatropha curcas oil, and at the same time promote the compatibility of the obtained modified graphene with components such as base oil. Sodium dodecylbenzene sulfonate, as an ionic surfactant, improves the compatibility of imidazole and 2-hydroxy-3-naphthoic acid borate in the ionic liquid on the surface of the modified graphene with the system, and jointly reduces the oil separation of the grease and the evaporation loss. The results of Examples 54, 60-62 show that PAO is added twice to prepare grease, and the first addition amount is controlled within the range of 1 / 20-2 / 5. The obtained grease has a small oil separation amount and a small evaporation loss. The steel mesh oil separation amount of the grease in Example 54 is the smallest. In Comparative Example 9, the first addition amount of PAO is 4 / 5 of its total mass, and the obtained grease has a high oil separation amount and evaporation loss. It is possible that the base oil is added in excess, and the reaction with the thickener and the groups on the surface of the modified graphene is too fast, resulting in a large difference in the synthesis rate of the grease. A small amount of base oil is added later, the grease is not fully synthesized, and the components are poorly combined, which ultimately leads to an increase in oil separation amount and evaporation loss. In summary, the steel mesh of the heavy-duty open gear graphene grease prepared by the present invention has a low oil separation amount, a small evaporation loss, and good stability of the grease.
[0148] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing heavy-load open gear graphene grease, characterized in that: The following steps are involved: Oxidizing graphite powder to obtain graphene oxide; adding 0.16-0.38 parts of octadecylamine, 1-hydroxybenzotriazole, 4-dimethylaminopyridine, 0.09-0.22 parts of trimethylsilyl chloride, DMF and hydrochloric acid to a mixture of the graphene oxide and water to obtain a modified graphene precursor; adding 0-0.21 parts of 1-methylimidazole to the modified graphene precursor to react to obtain a modified graphene intermediate 1; adding 0-1.35 parts of anionic salt to the modified graphene intermediate 1, and refluxing to obtain a modified graphene intermediate 2; Adding NH2-PEG-COOH solution to epoxidized jatropha oil to obtain NH2-PEG-COOH-JCOE solution; the amount of NH2-PEG-COOH solution added is 10.9-28.2 parts; adding 594-627 parts of phytic acid solution after heating, and performing vacuum distillation after reaction to obtain modified jatropha oil; Sodium dodecylbenzene sulfonate, Tween 80, the modified graphene intermediate 2, and the modified jatropha curcas oil in a mass ratio of 0.01-0.03:0.01-0.02:1:0.3 are placed in a ball mill to grind to obtain modified graphene; A mixture of PAO and 0-83 parts of alkyl naphthalene oil is used to obtain a mixed base oil; the PAO is 1 / 20-4 / 5 of the total added amount of PAO; after the temperature is raised to react, the modified graphene and 7.21-9.01 parts of a specific surface area of 100-300m 2 / g of thickener, the pH of the system is 3.0-5.0, and the temperature is raised to obtain a heavy-load open gear graphene grease precursor; the PAO, stearic acid and modified graphene are added, the temperature is raised to react, the temperature is lowered, additives are added, and the heavy-load open gear graphene grease is obtained by grinding; The total amount of modified graphene added is 0.05-0.40 parts; the total amount of PAO added is 0-83.0 parts; the grinding speed is 250-400 rpm, and the grinding time is 1.5-3.5 hours.
2. The method for preparing a heavy-load open gear graphene grease according to claim 1, characterized in that: The preparation method of the graphene oxide is as follows: concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 4:1 to obtain a mixed acid solution; 10.5 parts of the graphite powder and 8.0 parts of sodium nitrate are added to 0.7L of the mixed acid solution, and ultrasonically reacted for 2h to obtain a graphene oxide solution; the graphene oxide solution is centrifuged to obtain insoluble matter; The insoluble matter was washed with a hydrogen peroxide solution having a volume fraction of 30% and a hydrochloric acid solution having a volume fraction of 5%, and then repeatedly washed with deionized water, and dried to obtain graphene oxide.
3. The method for preparing a heavy-load open gear graphene grease according to claim 1, characterized in that: The anion salt is one of potassium hexafluorophosphate and 2-hydroxy-3-naphthoic acid borate; the preparation method of the 2-hydroxy-3-naphthoic acid borate comprises the following steps: Dispersing 0.76-1.15 parts of 2-hydroxy-3-naphthoic acid in 20 parts of DMF to obtain a 2-hydroxy-3-naphthoic acid solution; 0.30 parts of boric acid are dispersed in 10 parts of DMF to obtain an inorganic acid solution; the inorganic acid solution is added to the 2-hydroxy-3-naphthoic acid solution, and then 0.02 parts of lithium carbonate are added, the temperature is slowly increased to 30-60° C., and reflux reaction is performed until the pH value of the system is stable to obtain a product; The product is centrifuged, washed and dried to obtain the 2-hydroxy-3-naphthoic acid borate.
4. The method for preparing a heavy-load open gear graphene grease according to claim 1, characterized in that: The preparation method of the modified jatropha oil is as follows: adding jatropha oil to a three-necked flask, adding glacial acetic acid and concentrated sulfuric acid thereto under rapid stirring, mixing evenly, and heating to 30° C. to obtain the jatropha oil to be oxidized; dropping 35% hydrogen peroxide into the jatropha oil to be oxidized at a rate of 2 drops per second, heating to 65° C. and reacting for 4.5 hours, and obtaining the epoxidized jatropha oil after liquid separation and washing; adding 1 / 3 of the NH2-PEG-COOH solution into the epoxidized jatropha oil, reacting at a speed of 600 rpm for 6 hours, and then continuing to add 2 / 3 of the amino polyethylene glycol carboxyl solution. , after reacting for 15 hours, an amino polyethylene glycol carboxyl grafted epoxidized jatropha oil solution (NH2-PEG-COOH-JCOE) is obtained; the total amount of the amino polyethylene glycol carboxyl solution added is 10.9-28.2 parts; the NH2-PEG-COOH-JCOE solution is heated to 75°C, 594-627 parts of phytic acid solution are slowly added thereto, and after reacting for 24 hours, a PTE-NH2-PEG-COOH-JCOE solution is obtained; the PTE-NH2-PEG-COOH-JCOE solution is subjected to reduced pressure distillation to remove water, 5 parts of magnesium sulfate are added and dried for 12 hours to obtain the modified jatropha oil.
5. The method for preparing a heavy-load open gear graphene grease according to claim 1, characterized in that: The preparation method of the heavy-load open gear graphene grease is as follows: add the dodecyl hydroxystearic acid and the stearic acid and 0-83 parts of the alkyl naphthalene oil to the PAO to obtain a mixed base oil; the first addition amount of the PAO is 1 / 20-4 / 5 of the total addition amount of the PAO; the mixed base oil is heated to 90°C and maintained for 1 hour, and then 1 / 4 of the modified graphene and 7.21-9.01 parts of the alkyl naphthalene with a specific surface area of 100-300m 2 / g of the thickener, adjusting the pH of the system to 3.0-5.0, raising the temperature to 120°C, reacting for 2h to obtain the heavy-load open gear graphene grease precursor; adding the PAO to the heavy-load open gear graphene grease precursor, supplementing the stearic acid, and then adding 3 / 4 of the modified graphene, raising the temperature to 200°C, reacting for 20min, stopping heating and stirring, and when the temperature drops to 70°C, adding the additives thereto, stirring and mixing for 1h, and cooling to room temperature to obtain a heavy-load open gear graphene grease precursor; Gear graphene grease intermediate; the second addition amount of the PAO is 1 / 5-19 / 20 of the total addition amount of PAO by mass; the heavy-load open gear graphene grease intermediate is placed in a three-roll grinder, the grinding speed is 250-400rpm, the grinding time is 1.5-3.5h, and the heavy-load open gear graphene grease is obtained; the total addition amount of the PAO is 0-83.0 parts; the total addition amount of the modified graphene is 0.05-0.40 parts; the thickener is fumed silica.
6. The method for preparing a heavy-load open gear graphene grease according to claim 1, characterized in that: The 1-methylimidazole is 0.05-0.10 parts; the anion salt is 0.55-1.35 parts; and the alkyl naphthalene base oil is 23-30 parts.
7. The method for preparing a heavy-load open gear graphene grease according to claim 1, characterized in that: The first addition amount of the PAO is 1 / 20-2 / 5 of the total addition amount of the PAO by mass; the second addition amount of the PAO is 3 / 5-19 / 20 of the total addition amount of the PAO by mass.
8. The method for preparing a heavy-load open gear graphene grease according to claim 1, characterized in that: The additive comprises 0.1 part of nano-metal sulfide, 0.01-0.03 part of dibutyl dithiocarbamate oxymolybdenum, 0.01-0.04 part of 2-mercapto-1,3,4-thiadiazole, 0.03 part of trans-1,2-cyclohexanedicarboxylic acid, and 0.02 part of 2,5-2-mercapto-1,3,4-thiadiazole dimer.
9. The method for preparing a heavy-load open gear graphene grease according to claim 8, characterized in that: The nano-metal sulfide is one of nano-tungsten disulfide and nano-molybdenum disulfide; the particle size of the nano-tungsten disulfide is 500 μm; the particle size of the nano-molybdenum disulfide is 500 μm.
10. A heavy-load open gear graphene grease, characterized in that: The heavy-load open gear graphene grease comprises the modified graphene, the PAO, the alkyl naphthalene oil, the dodecyl hydroxystearic acid, the stearic acid, and the additive; the heavy-load open gear graphene grease is prepared by the preparation method according to any one of claims 1 to 9; the heavy-load open gear graphene grease has an average wear spot diameter of 0.296-0.491 mm and a friction coefficient of 0.02-0.09; the heavy-load open gear graphene grease P B The values are 1236N and 1569N, P D The values are 6080N and 7846N; the cone penetration of the heavy-load open gear graphene grease is 355-430 (0.1mm), and the dropping point is 220-329°C; the initial oxidation temperature of the heavy-load open gear graphene grease is 280°C-295°C, and the low-temperature similar viscosity at -40°C is 796-980Pa·s; the steel mesh oil separation of the heavy-load open gear graphene grease is 0.13%-0.27%, and the evaporation loss is 0.08%-0.33%.
Citation Information
Patent Citations
High-performance composite calcium sulfonate based lubricating grease and preparation method thereof
CN103146465A
Composition of food-grade lubricating grease and preparation method thereof
CN103789065A
Preparation method of graphene composite lubricating grease
CN111471510A
Preparation method of super-regular graphene-based lubricating grease
CN113214884A
Method for preparing graphene by using composite ionic liquid
CN113387348A
Cited By
High-temperature-resistant lubricant composition and preparation method thereof
CN119842430A
A high-temperature resistant lubricant composition and a preparation method thereof
CN119842430B